THE RELATIONSHIP OF KNOWLEDGE, ATTITUDES AND OWNERSHIP OF A latrine AND THE ACT OF OPEN DEFEATING IN SEI BILAH EAST DISTRICT LANGKAT DISTRICT YEAR 2024 - Sinaga , Lia Rosa Veronika; Veronica N, Ita; Munthe , Seri Asnawati; Manurung, Jasmen (Akupun Tour Publisher, 2024)
Background: Sanitation is one component of public health. Intentional behavior to promote clean living to prevent humans from coming into direct contact with dirt and hazardous waste materials. The behavior of defecating in open areas such as rivers or gardens has become a habit that is often carried out by the community. The habit of open defecation, which results in contamination of drinking water sources as well as recontamination of water sources and food eaten at home directly or indirectly. There are still people who do not have toilets at home or defecate in the open. Purpose: to determine the relationship between knowledge, attitudes and ownership of toilets with open defecation behavior in Sei Bilah Timur sub-district, Langkat Regency in 2024. Method: The type of research is an analytical survey with a cross sectional design. The population in this study is the II Mawar neighborhood in the working area of ​​the Community Health Center. The Old Village of Sei Lepan has 335 families. The sampling technique used is based on the Slovin formula. Based on the results of the research and discussion, it can be concluded that there is a relationship between knowledge and open defecation behavior in Sei Bilah Timur Village, Langkat Regency. with a P-Value of 0.000 or α<0.05, and also a relationship between attitudes and open defecation behavior in Sei Bilah Timur Village, Langkat Regency. with a P-Value of 0.000 or α<0.05 and there is a relationship between latrine ownership and open defecation behavior in Sei Bilah Timur Village, Langkat Regency. with a P-Value of 0.000 or α<0.05. Disscusion and Conclusion: It is recommended that the STBM program be developed from the Sei Bilah Timur Langkat Community Health Center for heads of families who do not yet have a latrine, especially a healthy latrine with a trigger system to increase latrine ownership in the working area of ​​the Sei Bilah Timur Langkat Community Health Center.